If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 7 = -1x + -15 Reorder the terms: 7 + 10x = -1x + -15 Reorder the terms: 7 + 10x = -15 + -1x Solving 7 + 10x = -15 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 7 + 10x + x = -15 + -1x + x Combine like terms: 10x + x = 11x 7 + 11x = -15 + -1x + x Combine like terms: -1x + x = 0 7 + 11x = -15 + 0 7 + 11x = -15 Add '-7' to each side of the equation. 7 + -7 + 11x = -15 + -7 Combine like terms: 7 + -7 = 0 0 + 11x = -15 + -7 11x = -15 + -7 Combine like terms: -15 + -7 = -22 11x = -22 Divide each side by '11'. x = -2 Simplifying x = -2
| 5x=234 | | 8z=9z-3 | | 7+3t-1=8t+24-2t | | 2[4-9x]=9x+7 | | -143=3(-6b-1)+4 | | 6(5y-8)-(7y+4)= | | 9x^2+13=247 | | -4(1-5v)=-144 | | 7+5[1+2(2x+5)]=6(x+7) | | P-16=13-6p | | 4c+1-c=19 | | (x+5)(x-2)=35 | | 8b-5b-7=23 | | 8y+4y=144 | | 2.5[x+3(x+7)]= | | 6x+8y=-11 | | (3a)+(2a-25)=180 | | .50(x-2)=4x-0.2222x-4 | | 5(3b-4)=40 | | 3(4x+3)=17 | | 6r+5=4(r+2)-2r | | 2yf-3(2y-3)+2=31 | | F(x)=x^3+2x^2+x+4 | | 2n-1=-10 | | 11=4(x-1)-x | | 2600=(2x-6)m+(x+3)m | | 4x+5=16x+8-12x-3 | | 1.8x+2.8=2.5*2.1 | | -108=3(4+8n) | | 2[4x+1]+5=19 | | (8x-12)(5x-25)=0 | | (a)3.43x=5.6 |